Developing a Value Clarification Technique (VCT) Learning Model to Enhance Nationalism Attitudes of Elementary School Students: A Sustainable Educational Management Perspective - Yanuarius Bria Seran (Universitas Negeri Jakarta, 2025)
Background: The inadequacy of Pancasila and Civic Education (PPKn) instruction, which remains predominantly cognitive and lecture-based, thereby limiting internalization of nationalistic values among elementary school students, constitutes the main problem addressed in this study.Purpose:This study aims to develop a Value Clarification Technique (VCT) learning model to enhance nationalistic attitudes among elementary school students.Design/method/approach:Using a systematic literature review of peer-reviewed articles published between 2020 and 2025, this study identified, selected, evaluated, and synthesized relevant findings on VCT implementation in primary education.Results:Results demonstrate that the VCT model effectively cultivates nationalist attitudes through five structured stages: value stimulus presentation, value exploration, discussion-based clarification, value-based decision-making, and reflection. This model promotes active student participation in value learning, producing deeper internalization of national character than conventional methods. Integration of contextual learning media within VCT further enhances student motivation and participation.Contribution/value:The novelty of this study lies in positioning VCT within a sustainable educational management framework and examining the interconnected roles of instructional leadership, teacher professional development, and strategic resource management in systematic character education. Implications for the Merdeka Curriculum’s Pancasila student profile are discussed.